« НазадПродовжити »
ON THE TANGENTS, NORMALS AND ASYMPTOTES TO CURVES.
If the equation to the curve be put under the form
y = f (x),
u = Q(x, y) = C, the equation to the tangent takes the more symmetrical form
dy If u be a homogeneous function of n dimensions in x and y, by a well-known property of such functions
(x' - x);
= nu = nc,
The length of the subtangent is y
dx dy dy
The length of the subnormal is y
idx) The length of the tangent is ข +
dy The length of the normal is +
The perpendicular from the origin on the tangent is
+ Y ydx - ady
dy p = (dx* + dys)!
dy if u be a homogeneous function of n dimensions in w and y.
The portion of the tangent intercepted between the point of contact and the perpendicular on it from the origin is
dy The portions of the axes cut off between the origin and the tangent, or the intercepts of the tangent, are
dy Y - X
along the axis of y. dx
These I shall call y, x, respectively.
Ex. (1). The equation to the hyperbola referred to its asymptotes is
X Y = m*.
= x, and the equation to the tangent is
y (a' – x) + x (y' - y) = 0;
- y dx
dy ma as X Y = ma.
2 m2 The perpendicular on the tangent p =
(x® + yo)!
4 ma is constant ; and the triangle contained between the axes and the tangent, being proportional to this product, is also constant.
(2) The equation to the parabola referred to two tangents as axes is
Hence the equation to the tangent is
b or X, Y, are the co-ordinates of the chord joining the points at which the axes touch the curve.
(3) The equation to one of the hypocycloids referred to rectangular co-ordinates is
x} + y} = a). The equation to the tangent is
y Therefore ~, = aš rl, y, = ašys; and the portion of the tangent intercepted between the axes = (x + + y.3)} = a; or the hypocycloid is constantly touched by a straight line of given
length which slides between two rectangular axes. The converse of this proposition, viz. that the locus of the ultimate intersections of a line of given length sliding between rectangular axes is this hypocycloid, was first shewn by John Bernoulli. (See his Works, Vol. 1. p. 447.)
For the perpendicular from the origin on the tangent we find
p = (a xy). (4) In the cissoid of Diocles,
2a - X
The subtangent = a, and is therefore constant.
(y - c*)?
(7) From the general parabolic equation
y = am-1x, we find the equation to the tangent to be
mx (y' – y) = y (x' – x).
AB (fig. 19) being the axis of x.
If M be the point where the ordinate meets the generating circle, and if we join MA, MB, then
MN (20 x – ?)? dy
dix That is to say, the tangent to the cycloid is parallel to the chord of the generating circle. The normal is evidently parallel to the other chord MB. Hence also the angle which two tangents make with each other is equal to the angle between the corresponding chords of the generating circle.
y = Y - (2a w – xo)! = PN - MN = PM. But from the generation of the curve, PM is equal to the arc of the circle AM, therefore y. = arc AM.